SURVEY ON AIS BASED COMPUTER SECURITY SYSTEM - S Monica Catherine, Ms; Mondal, Soumik (International Journal of Engineering and Technology, 2018)
Â Â Â Â Â Artificial intelligence is gaining popularity in wide area of technology. Now days due to increase in computerized system of every field, security of any computer system is a big concern. In recent days, the artificial intelligence is emerging in computer security field, which evolves the computer security in a new way. In the last few years artificial immune system has been applied in various fields. It is a very effective technology to detect anomalous behaviour in the computer system, especially in computerâ€™s security domain. Artificial Immune System is a new bio-inspired model, which grab the attention of researchers to solve various problems in Information Security field. The unique feature of AIS is very promising to solve various issues in security field. A survey on current existing security technique based on Artificial Immune System is presented in this paper.Â Â